Cap Assisted Upper Endoscopy for Examination of the Major Duodenal Papilla: A Randomized, Blinded, Controlled Crossover Study (CAPPA Study) - Abdelhafez, Mohamed; Phillip, Veit; Hapfelmeier, Alexander; Elnegouly, Mayada; Poszler, Alexander; Strobel, Kilian; Born, Peter; Dollhopf, Markus; Kassem, Abdel Meguid; Calavrezos, Lenika; Klare, Peter; Schlag, Christoph; et al. (The American journal of gastroenterology, 2017)
Examination of major duodenal papilla (MDP) by standard forward-viewing esophagogastroduodenoscopy (S-EGD) is limited. Cap assisted esophagogastroduodenoscopy (CA-EGD) utilizes a cap fitted to the tip of the endoscope that can depress the mucosal folds and thus might improve visualization of MDP. The aim of this study was to compare CA-EGD to S-EGD for complete examination of the MDP. Prospective, randomized, blinded, controlled crossover study. Subjects scheduled for elective EGD were randomized to undergo S-EGD (group A) or CA-EGD (group B) before undergoing a second examination by the alternate method. Images of the MDP were evaluated by three blinded multicenter-experts. Our primary outcome measure was complete examination of the papilla. Secondary outcome measures were duration and overall diagnostic yield. A total of 101 patients were randomized and completed the study. Complete examination of MDP was achieved in 98 patients using CA-EGD compared to 24 patients using S-EGD (97 vs. 24%, P<0.001). Median duration from intubation of the esophagus until localization of the MDP was shorter with CA-EGD (46. vs. 96 s., P<0.001). In group A, 11 extra lesions and 12 additional incidental findings were detected by secondary CA-EGD, whereas neither were detected by secondary S-EGD in group B (22 vs. 0% and 24 vs. 0%, P<0.001 and P<0.001). CA-EGD enabled complete examination of MDP in almost all cases compared to a low success rate of S-EGD. CA-EGD detected a significant amount of lesions and incidental findings when added to S-EGD. CA-EGD is a safe and effective method for examination of MDP.